2013
DOI: 10.3944/aott.2013.3103
|View full text |Cite
|
Sign up to set email alerts
|

Etiology of coxarthrosis in patients with total hip replacement

Abstract: Despite the heterogeneity of our study population, our results may reflect the distribution of coxarthrosis etiologies in Turkey. Developmental dysplasia of the hip appears to be the most frequent cause of coxarthrosis among the patients undergoing total hip replacement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 8 publications
1
16
0
4
Order By: Relevance
“…23 Uluçay et al reported that in 886 patients with THA due to coxarthrosis, 75% was female with 24.7% male. 21 In our study, when the opposite hips of patients with CE angle below 20 are investigated, 91% also had CE angle below 20 in the opposite hip; in other words, they were dysplastic.…”
Section: Discussionmentioning
confidence: 57%
“…23 Uluçay et al reported that in 886 patients with THA due to coxarthrosis, 75% was female with 24.7% male. 21 In our study, when the opposite hips of patients with CE angle below 20 are investigated, 91% also had CE angle below 20 in the opposite hip; in other words, they were dysplastic.…”
Section: Discussionmentioning
confidence: 57%
“…One of the most common adolescent hip conditions is slipped capital femoral epiphysis (SCFE), whereby the proximal femoral epiphysis shifts into a varus malalignment through the proximal femoral physis, with an estimated prevalence of 1 to 10 per 100 000 children (Figure 1A). Given the resultant hip malalignment seen in patients with SCFE, this condition is thought to be a factor in up to 25% of degenerative hip disease in adults requiring total hip arthroplasty . In most cases, this deformity can be successfully treated with a percutaneously placed single cannulated screw to stabilize the deformity in an in situ fashion (Figure 1B).…”
Section: Introductionmentioning
confidence: 99%
“…9,10 The incidence of hip involvement in AS ranges from 30% to 50% of patients, and THA is performed to improve pain, stiffness, and disability of the involved hips of AS patients. 11,12 To date, no studies have examined sexual activity before and after THA in male AS patients with hip involvement. Therefore, this current study aimed to evaluate the effect of THA on sexual activity and to explore the most commonly reported and comfortable coital position for male AS patients with hip involvement.…”
Section: Introductionmentioning
confidence: 99%